Synthesis, characterization, anti-cancer evaluation, and DNA-binding study of new bay-substituted perylene derivatives - Arwa Abourajab; S Melika Mostafanejad; Meltem Dinleyici; Basma Al-Khateeb; Imge Kunter; Sukru Tuzmen; Huriye Icil (Journal of Biology and Medicine - Peertechz Publications, 2023)
Two new perylene derivatives 1,7-di(3,5-diamino-pyrimidoxyl) perylene-3,4,9,10- tetracarboxylic acid bisanhydride (4) and 1,7-di(2-[3-[(4-amino-2-methylpyrimidin-5-yl)methyl]-4-methyl-1,3-thiazol-3-ium-5-yl]) ethoxyperylene-3,4,9,10-tetracarboxylic bisanhydride (6) have been synthesized. We aimed to study their interactions with G-quadruplex (G4) structures as potent G4 ligands and telomerase inhibitors. We used a PCR-amplified guanine-rich region from the human beta-globin gene, oligonucleotide from human telomeres (a-coreTT), an oncogene (c-kit), and SK-HEP-1 adenocarcinoma cells to characterize those compounds' binding and stabilizing abilities to G4 structures and anti-cancer potential. All results obtained through UV-visible and fluorescence spectroscopies, agarose gel electrophoresis, and MTT assay on SK-HEP-1 adenocarcinoma cells were in good agreement. Compounds 4 and 6 are promising DNA-binding and cytotoxic compounds with a relatively antiproliferative effect on the selected tumour. In all studies, the formal positive charge carrier, compound 6, showed higher activity in terms of anti-cancer effects. These results may help elucidate the feasibility of the perylene derivatives as future chemo-therapeutic agents.